The Magic Key - Hunt, Roderick (Karachi Oxford University Press, 2012)
When the magic key takes the children into an adventure, they find themselves in a medieval world filled with knights, dragons, and mysteries.
Second edition, illustrated
Stage 5-Green book band
Keywords: Reading (Elementary)-Children's stories; Fiction